ANALISIS KINERJA BIDAN DESA DALAM PELAYANAN NEONATUS DI WILAYAH PUSKESMAS KABUPATEN LUMAJANG JAWA TIMUR - J Jamhariyah (Jurnal Ilmu Kesehatan Masyarakat, 2013)
Lumajang health center data of 2007-2010 showed that the results of the coverage of neonatal doesn’t reach  the target SPM (Minimum Service Standards). Based on a preliminary survey showed that the performance of village midwives in neonatal care not match with the standard set in the SPM, recording the results of neonatal care have not been implemented properly, not maximum utilization of facilities and supervision of the activities carried out by the report results. The aim of this study is to explain how the performance of village midwives in neonatal care in Lumajang. The kind of the research is qualitative descriptive study with cross sectional approach. Main informants is village midwife in Lumajang, by using a purposive sample of 25 sampling.Data collected through in-depth interviews  and data processing using the method of content analysis. The results obtained indicate that the performance of village midwives in neonatal care have good standards of tools, services and service schedules, optimal utilization of funds and facilities are not available yet evenly. Supervision needs to have appropriate midwives in neonatal care activities and interpersonal relationships is not maximized.